Postoperative control of liposuction pain - Marcel Vinicius de Aguiar Menezes; Priscila Teles Archanjo; Raquel Santana Ramos Oliveira; Lúcio Antonio Garcia Dias; José Siqueira Prado; Fernando Vicente de Araujo; Jessica Gonçalves de Queiroz (Revista Brasileira de Cirurgia Plástica)
INTRODUCTION: Pain control is essential in any surgical event. Liposuction is, in general, accompanied by complaints of post-operative pain, which raises the discussion about the best way to prevent and treat it. Accordingly, studies indicate that the analgesia should begin before any painful stimulus is triggered in order to reduce or prevent the pain preemptively. The approach of the various pain pathways, with a combination of different classes of drugs or utilization of spinal block or epidural/general anesthesia can also contribute to pain management. METHODS: A descriptive, prospective, interventional cohort type study was conducted with patients undergoing plastic surgery involving liposuction. The standard anesthetic procedure consisted of an association between general and spinal anesthesia. The assessment of pain, carried out 6 and 18 hours after the end of the surgery, used unidimensional scales. The absence of pain or the presence of mild pain was considered a satisfactory result. RESULTS: Fifty female patients were evaluated, with an average of 35 years of age. No intense pain was found at any time during the study. Satisfactory results accounted for 94% and 92% of the patients in the assessment at 6 and 18 hours post-surgery, respectively (p < 0.001). CONCLUSIONS: Intravenous anesthesia combined with spinal anesthesia, in body contouring surgery, was able to satisfactorily control pain in the immediate postoperative period in most cases (>90%). In this study, liposuction was revealed to be a type of surgery with manageable pain.